A low-dielectric decoration strategy to achieve absorption dominated electromagnetic shielding material. (15th February 2020) - Jia, Zirui; Wang, Chao; Feng, Ailing; Shi, Pengbao; Zhang, Chuanhui; Liu, Xuehua; Wang, Kuikui; Wu, Guanglei
Abstract: The shielding mechanism for conversional electromagnetic shielding material is mainly dependent on the reflection, thus the electromagnetic interference (EMI) or pollution can't be really solved, owing to the 2nd interference or pollution. To overcome this barrier, we developed an absorption dominate EMI shielding material, using low permittivity component (TiO2, amorphous carbon and SiO2 ) to decorate magnetic carbonyl iron (CIF). Consequently, the impedance matching ability can be greatly improved, simultaneously showing desirable dual magnetic and dielectric loss ability. The varied morphology, crystal phases and EMI shielding performance of resultants have been well studied. It has been confirmed that the reflection coefficient of SiO2 decorated CIF sample could be reduced from 90 to 56.6%, suggesting the improved EM absorption ability. Meanwhile, it corresponding absorption coefficient could up to 43.3%, which is also much better than TiO2 or amorphous decorated CIF. The method for the successfully use low-dielectric component to decorate magnetic metal has been demonstrated as a useful strategy for the preparation of achieving absorption dominate EM shielding material. Graphical abstract: Carbonyl iron decorated by the component with low dielectric exhibits excellent absorption dominate electromagnetic shielding performance. Image 1 Highlights: Low-dielectric component (SiO2, C and TiO2 ) can be easily coated on carbonyl iron. The as-prepared shows dual magnetic and dielectric loss ability. The impedance matching ability can be greatly improved. The optimal sample has an excellent absorption dominate ability with a absorption coefficient of 43.3%. The total shielding effectiveness was ~29 dB under a thickness of 1.5 mm.